A NOSOCOMIAL INFECTION MANIFESTED AS ERYSIPELAS IN PEMPHIGUS FOLIACEUS PATIENT UNDER INTRAVENOUS DEXAMETHASONE TREATMENT - Pranata, Achmad Yudha; Gunawan, Hendra; Sutedja, Endang; Suwarsa, Oki; Dharmaji, Hartati Purbo (Institute of Topical Disease Universitas Airlangga, 2016)
Introduction: Puncture wound in diagnostic interventions permits the entry of bacteria into the skin or soft tissue, thus precipitating nosocomial infection, such as erysipelas. There are other risk factors of nosocomial infections including old age, immunosuppressive drugs, and underlying diseases. Pemphigus foliaceus (PF) is an autoimmune disease with corticosteroid treatment as the mainstay therapy, which could cause immunosuppression and predispose patients to infection. The objective of this paper was to report erysipelas as one of the manifestations of nosocomial infection in patients under immunosuppressive therapy. Case: A case of erysipelas acquired on the 9th day of hospitalization in a PF patient underwent intravenous dexamethasone injection, with history of puncture wounds on the previous day on the site of erysipelas was reported. The clinical findings of erysipelas were well defined, painful erythema and edema that felt firm and warm on palpation, with blisters and pustules on top. Gram staining from the pustules and blisters fluid revealed Gram (+) cocci. Patient was given 2 grams intravenous ceftriaxone for 7 days and saline wet compress. Improvement on the erysipelas was seen the day after ceftriaxone injection. The patient was discharged after 12 days of hospitalization with improvement both on the PF and the erysipelas. On the next visit 7 days later, the erysipelas lesion disappeared. Conclusion: Puncture wound and immunosuppresive treatment are the factors that could cause erysipelas as a nosocomial infection, and an appropriate treatment of the infection would decrease the functional disability of the patient.